'They Walked Towards Their Death As If to a Party.' Martyrdom, Agency and Performativity in the Spanish Civil War*. (2nd July 2016) - Ramón Solans, Francisco Javier
ABSTRACT: Despite the great number of articles and publications on anticlerical violence during the Spanish Civil War, this is the first to focus on the perceptions of its victims. In the documents they left behind, these imprisoned clergymen represented themselves as martyrs. With no influence from rebel propaganda, these statements provide evidence that the rhetoric of martyrdom was embedded in Spanish Catholic culture prior to the coup d'état against the Second Republic in 1936. Through a case study of the Roman Catholic Diocese of Barbastro, one of the districts most disrupted by anticlerical violence, this article explores the existence of a Catholic agency which transformed death in the name of God into a path of perfection; a path toward the improvement of oneself and of the whole of society. They thought of their martyrdom as a contribution to the victory of the rebels that would bring the Kingdom of God closer to Spain. Imbued by this ideal they performed their own martyrdom.